DExPO project (2022-23): Dolphin exploitation in prehistoric oman - Maini, Elena (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Prehistoric communities along the coasts of southeastern Arabia relied heavily on marine resources. However, dolphin remains in the zooarchaeological record remain poorly understood due to fragmentation, taphonomic changes, limited osteological collections, and the lack of a specific methodology for determination. In response to these challenges, the DExPO project aimed to develop a protocol for the analysis of osteological data from odontocetes and cetaceans from Late Neolithic and Early Bronze Age sites in central Oman. Agreements with the Ministry of Heritage and Tourism along and support from the Natural History Museum of Oman facilitated the project. Initial implementation took place in a pilot project (2019-2020) on cetaceans in the NHM collection, and has been extended to analyse archaeological remains from key sites in Ash-Sharqiyah Governorate. Ongoing objectives include developing a methodology for identifying and documenting archaeological dolphin remains and applying these methods to large osteological collections. This is central to the study of dolphin hunting and exploitation strategies, combining zooarchaeological, material culture and environmental data, using ethnographic parallels and experimental approaches. Through the DExPO project, the enigmatic relationship between prehistoric communities and marine mammals is gradually being unravelled, providing insights into their ancient coexistence along the coasts of the Arabian Sea.
Keywords: Archéologie – Oman